PENGARUH CELEBRITY ENDORSER NAGITA SLAVINA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE MS GLOW PADA MAHASISWA STIE PANCASETIA BANJARMASIN - Norhidayati Norhidayati; Rifqi Amrulloh (STIE Mahardhika, 2022)
The purpose of this study was to determine the credibility, attractiveness, and popularity simultaneously and partially have a positive and significant effect on purchasing decisions for MS GLOW Skincare Products at STIE Pancasetia Banjarmasin students and then to determine which variables have a dominant influence on purchasing decisions for MS GLOW Skincare Products.The method used is multiple linear regression analysis. This research was conducted on 254 students with a sample of 147 STIE Pancasetia Banjarmasin students who had used MS GLOW Skincare Products. Collecting data using a questionnaire distributed via Google Form with a measurement of 5 likert scale.The results show that 1. The variables of credibility, attractiveness, and popularity simultaneously have a positive and significant effect on purchasing decisions for MS GLOW Skincare Products where the value of Fcount > Ftable (82,023 > 2,67) with a significant level of 0.000 < 0.05. 2. The credibility variable with a value of tcount > t table (5.345 > 1.977) with a significant level (0.000 < 0.05), the attractiveness variable with a value of tcount > t table (3.481 > 1.977) with a significant level of 0.001 < 0.05, the popularity variable with the value of tcount > t table (4.697 > 1.977) with a significant level of 0.000 < 0.05 partially has a positive and significant effect on purchasing decisions for MS GLOW Skincare Products. 3. The variable that has the dominant influence on purchasing decisions for MS GLOW Skincare Products is credibility (X1) which has the largest value, which is 0.410.